Static data ageing techniques: Accounting for population changes in tax-benefit microsimulation models - Herwig Immervoll; Klas Lindström; Esko Mustonen; Marja Riihelä; Heikki Viitamäki (University of Essex, Institute for Social and Economic Research (ISER), 2005)
Tax-benefit microsimulation models are frequently used to analyse the distributional, budgetary and behavioural effects of social and fiscal policies in a period t* using data from some previous period that have been adjusted (“aged”) to approximate the population in period t*. This paper considers which types of data adjustments are necessary and appropriate and discusses issues and limitations that affect the scope and interpretation of results based on aged data. It presents a simple conceptual framework for thinking about different types of data adjustments and illustrates the mechanics of ageing procedures in a case study using the EUROMOD tax-benefit model in conjunction with detailed Finnish household micro-data from two periods (1996 and 1998). The case study evaluates the performance of one particular ageing technique by comparing results from the 1998 dataset with those derived from aged 1996 data.
Keywords: C81; C88; 330; Data Ageing; Re-weighting; Microsimulation; Tax-Benefit Model